A decade of German Engineering Education collaboration: past, present and future - Muhammad Hafiz Aswad, Ahmad Kamal (2020)
The year 2020 marks a milestone in the history of academic collaboration between Universiti Malaysia Pahang (UMP) and its German partners, the Karlsruhe University of Applied Sciences (HsKA) and Reutlingen University (HsRT). Back in 2009, the Malaysian Government instructed the Malaysian Technical Universities Network (MTUN) to model their programmes similar to the Fachhochschule programme in Germany